Implementation of Computer Vision for Efficient Attendance and School Uniform Checking System - Maulana, Faris; Sinaga, M. Ali Akbar; Rizal, Hairul; Mahendra, Bella Nideni; Anggraini, Lita; Amartiwi, Utih (Tauladan Fathimah Azzahra, 2023)
Managing school administrative tasks can consume substantial time and effort. Every semester, teachers find themselves occupied in repetitive manual tasks such as attendance tracking, disciplinary documentation, and assignment grading. These sometimes could take longer time than preparation for teaching. In this research, we proposed an Artificial Intelligence (AI) approach to handle this problem. In the era of Industry 4.0, AI has been managed to be personal assistance and do human repetitive tasks efficiently. However, the implementation of AI in Indonesia especially for educational institutions is still rare. Therefore, we have developed an innovative AI-driven attendance and uniform detection system by implementing computer vision models. Computer vision is a field of AI that equips machines with the ability to interpret and understand visual information from images and videos, enabling them to classify images and detect objects. The results show that computer vision has successfully facilitated swift and accurate detections for this task. We have also incorporated a timestamp to provide information about the time when students arrive at school. Subsequently, all the recorded data will be saved and organized within the school’s database. As a result, teachers are liberated from the tedium of manual data entry and can redirect their efforts toward pedagogical materials and instructional strategies.